2008
DOI: 10.1523/jneurosci.1893-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Aging: A Common Decline of Episodic Recollection and Spatial Memory in Rats

Abstract: In humans, recognition memory declines with aging, and this impairment is characterized by a selective loss in recollection of previously studied items contrasted with relative sparing of familiarity for items in the study list. Rodent models of cognitive aging have focused on water maze learning and have demonstrated an age-associated loss in spatial, but not cued memory. The current study examined odor recognition memory in young and aged rats and compared performance in recognition with that in water maze l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
77
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 63 publications
16
77
0
Order By: Relevance
“…In addition, functional imaging studies have reported double dissociations between brain areas activated in association with recollection-or familiarity-driven memory (e.g., Ranganath et al 2004;Yonelinas et al 2005Daselaar et al 2006;Montaldi et al 2006; but see Shrager et al 2008; for review, see Eichenbaum et al 2007). Also, the ROC index of recollection for the recognition of single items was eliminated, while the familiarity was enhanced in aged rat animals that performed exceptionally in overall accuracy (Robitsek et al 2008). Furthermore, in associative recognition, hippocampal damage reduced the ROC index of recollection but enhanced that of familiarity (Sauvage et al 2008), consistent with the findings that hippocampal damage results in the unitization of stimulus features, allowing familiarity to support recognition of each unitized stimulus configuration (Quamme et al 2007).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, functional imaging studies have reported double dissociations between brain areas activated in association with recollection-or familiarity-driven memory (e.g., Ranganath et al 2004;Yonelinas et al 2005Daselaar et al 2006;Montaldi et al 2006; but see Shrager et al 2008; for review, see Eichenbaum et al 2007). Also, the ROC index of recollection for the recognition of single items was eliminated, while the familiarity was enhanced in aged rat animals that performed exceptionally in overall accuracy (Robitsek et al 2008). Furthermore, in associative recognition, hippocampal damage reduced the ROC index of recollection but enhanced that of familiarity (Sauvage et al 2008), consistent with the findings that hippocampal damage results in the unitization of stimulus features, allowing familiarity to support recognition of each unitized stimulus configuration (Quamme et al 2007).…”
Section: Discussionsupporting
confidence: 71%
“…Although speeding responses significantly reduced the contribution of the recollection process to odor recognition memory (P = 0.003), the reduction in the recollection index R was slightly less than that in aged rats or in rats with hippocampal damage performing on the same task (R young À R old = 0.27 > R sham À R hippocampus = 0.23 > R no deadline À R deadline = 0.20) (Fortin et al 2004;Robitsek et al 2008). The smaller number of subjects used in the present study could account, at least in part, for this result.…”
Section: Discussionmentioning
confidence: 99%
“…many of the memory problems reported with increasing age. Aging is associated with a decline in episodic memory formation (37), spatial memory and navigation (38), contextual source memory (39), and recollection (40,41). These functions require intact pattern separation circuitry (7,42).…”
Section: Discussionmentioning
confidence: 99%
“…Spatial memory deficits have been considered to parallel episodic memory or recollection deficits in humans (Robitsek et al 2008;Tomás Pereira and Burwell 2015). Therefore, a test of whether changes in discrimination ability contribute to broader changes in mnemonic ability across the lifespan would be to assess both spatial memory and spatial discrimination performance in the same cohort of aged rats.…”
mentioning
confidence: 99%